TEACHING IN PANDEMIC TIMES, INSPIRATION FOR CHANGE: (Elena Onchevska-Ager and Ruska Ivanova-Naskova, Teaching in Pandemic Times: Experiences and Lessons from the Study of Students’ and Teachers’ Opinions at the Blazhe Koneski Faculty of Philology, Skopje, 2023, pp. 120) (Journal of Contemporary Philology, 2024)
(Елена Oнчевска-Агер и Руска Иванова-Наскова, Настава во пандемија: искутва и поуки од истражувањето на ставовите на студентите и наставниците на Филолошкиот факултет „Блаже Конески“, Скопје, 2023, 120 стр.)
Keywords: Приказ